Fuzzy-PID control algorithm of a loop reactor for microbial corrosion testing - Rangel-Miranda, D.; Alaniz-Lumbreras, D.; Castano, Victor (International Journal of Engineering and Technology, 2015)
The thermal control of loop reactor utilized to run hydrodynamic tests of microbical corrosion, where full control of the temperature is crucial, is presented. Since the accuracy of the temperature is critical along the pipe trajectory for the microbial culture, it must be controlled with an accuracy of Â± 0.5Â°C, which is achieved by an implemented fuzzy-PID (Proportional Integral and Derivative) control algorithm, capable to provide the accuracy at the temperature range required. The system counts with an especially-designed software to program the desired temperature. Several tests were carried out at different temperatures and water volumes to characterize the rising time and thermal inertia presented by the system. As a result, the performance and power consumption were notability improved.